SOCIO-ENVIRONMENTAL CERTIFICATIONS IN AGRI-FOOD SYSTEMS: CONVERGENCES AND DIVERGENCES OF ATTRIBUTES - Scalco, Andrea Rossi [UNESP] (Univ Federal Fluminense, Escola Engenharia, Dept Engenharia Producao, 2019)
Food products with socioenvironmental seals differ from conventional ones because they follow standards determined by regulators that issue certificates that guarantee that the productive practices, whether in agriculture or in their processing, protect the environment, preserve the health of the consumer and the worker, and respect human rights. Farmers/processors who seek certification and are in compliance with the standards may use the socio-environmental seal on their products. Because of the profusion of social and environmental seals, they can often confuse consumers with regard to their requirements. In this sense, this article was based on the investigation, through a content analysis, of the requirements of the three main socio-environmental certifications present in Brazil: organic system, ISO 14001 and Fair Trade. An analysis of the content addressed in the requirements of these socio-environmental certifications was carried out through its norms in order to identify the attributes, allowing ascertaining which aspects are convergent and which are divergent between the three certifications. The requirements of the standards were categorized in: Compliance with environmental legislation; Sustainable practices; Preservation of biodiversity; Sustainable development; Compliance with labor legislation; Fair trade; Social responsibility; Traceability; Non-genetically modified organisms; Environmental policy; Regional production and trade; Non-use of synthetic materials; and Free from contaminants. It was observed the divergence of the attributes present in the certifications studied, explaining the diversities of each of them, even in the convergent attributes, taking into account their particularities.
Keywords: Socio-environmental Certification; Product Quality; Seals